2000
DOI: 10.1097/00006982-200007000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Ocular and Orbital Blood Flow in Cigarette Smokers

Abstract: The authors believe that the decrease in the flow velocity of these vessels may be due to an increase in the vascular resistance of the vessels of the retina and optic nerve head in smokers. This may be important in patients with eye disease in whom altered blood flow already contributes to the ocular or orbital pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The major blood supply to the retina is the choroid, especially in darkness, where 90% of the oxygen comes from choroidal circulation [23]. In the literature, Bourke et al defined the correlation between untreated systemic hypertension and choroidopathy [24], Regatieri et al defined CT in diabetic retinopathy and suggested that CT was associated with retinal tissue hypoxia [25], and Steigerwalt et al and Sızmaz et al reported a decrease in CT in patients who smoked cigarettes, due to the increase in vascular resistance of the vessels [26,27]. According to the before-mentioned studies, migraine is known to be a neurovascular disease, and is known to reduce the blood flow at the level of the central retinal artery and posterior ciliary artery; the thinning of the choroid layer is an expected clinical outcome in migraine patients.…”
Section: Discussionmentioning
confidence: 99%
“…The major blood supply to the retina is the choroid, especially in darkness, where 90% of the oxygen comes from choroidal circulation [23]. In the literature, Bourke et al defined the correlation between untreated systemic hypertension and choroidopathy [24], Regatieri et al defined CT in diabetic retinopathy and suggested that CT was associated with retinal tissue hypoxia [25], and Steigerwalt et al and Sızmaz et al reported a decrease in CT in patients who smoked cigarettes, due to the increase in vascular resistance of the vessels [26,27]. According to the before-mentioned studies, migraine is known to be a neurovascular disease, and is known to reduce the blood flow at the level of the central retinal artery and posterior ciliary artery; the thinning of the choroid layer is an expected clinical outcome in migraine patients.…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress products lead to abnormal nitric oxide activity, vasomotor dysfunction, smooth muscle proliferation, inflammatory cells, and thrombocyte activation. 17 These effects on the circulatory system lead to ischemia and hypoxia in the tissue of cigarette smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking reduces retinal blood flow and hyperoxia autoregulation ability of retinal vessels due to the vasoconstrictive influences of nicotine and changed endothelial function. 25,26…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained indicate that patients often conceal the fact of their exposure to smoke. To our knowledge, no publications evaluate the impact of smoking on BRB function; however, there are studies dealing with the influence of smoking on vascular endothelium and discussing the impact of smoking on retinal function [16, 17]. BRB integrity is related to the function of the vascular endothelium; therefore one can expect that smoking and increased oxidative stress influence BRB function.…”
Section: Discussionmentioning
confidence: 99%